Pupil dynamics during very light exercise predict benefits to prefrontal cognition - Kuwamizu, Ryuta; Yamazaki, Yudai; Aoike, Naoki; Hiraga, Taichi; Hata, Toshiaki; Yassa, Michael A.; Soya, Hideaki (NeuroImage (Orlando, Fla.), 2023)
•We examine the effect of very light exercise on pupil size and prefrontal function.•Very light exercise improved executive function and task-related neural activation.•Pupil dilation mediated beneficial effects of exercise on executive function.•Pupil-linked neural substrate may account for cognitive potentiation post-exercise. Physical exercise, even stress-free very-light-intensity exercise such as yoga and very slow running, can have beneficial effects on executive function, possibly by potentiating prefrontal cortical activity. However, the exact mechanisms underlying this potentiation have not been identified. Evidence from studies using pupillometry demonstrates that pupil changes track the real-time dynamics of activity linked to arousal and attention, including neural circuits from the locus coeruleus to the cortex. This makes it possible to examine whether pupil-linked brain dynamics induced during very-light-intensity exercise mediate benefits to prefrontal executive function in healthy young adults. In this experiment, pupil diameter was measured during 10 min of very-light-intensity exercise (30% V˙o2peak). A Stroop task was used to assess executive function before and after exercise. Prefrontal cortical activation during the task was assessed using multichannel functional near-infrared spectroscopy (fNIRS). We observed that very-light-intensity exercise significantly elicited pupil dilation, reduction of Stroop interference, and task-related left dorsolateral prefrontal cortex activation compared with the resting-control condition. The magnitude of change in pupil dilation predicted the magnitude of improvement in Stroop performance. In addition, causal mediation analysis showed that pupil dilation during very-light-intensity exercise robustly determined subsequent enhancement of Stroop performance. This finding supports our hypothesis that the pupil-linked mechanisms, which may be tied to locus coeruleus activation, are a potential mechanism by which very light exercise enhances prefrontal cortex activation and executive function. It also suggests that pupillometry may be a useful tool to interpret the beneficial impact of exercise on boosting cognition. [Display omitted]